Cytosporin Derivatives from Arctic-Derived Fungus Eutypella sp. D-1 via the OSMAC Approach - Hao-Bing Yu; Zhe Ning; Bo Hu; Yu-Ping Zhu; Xiao-Ling Lu; Ying He; Bing-Hua Jiao; Xiao-Yu Liu (Marine Drugs, 2023)
A chemical investigation of the Arctic-derived fungus Eutypella sp. D-1 based on the OSMAC (one strain many compounds) approach resulted in the isolation of five cytosporin polyketides (compounds 1–3 and 11–12) from rice medium and eight cytosporins (compounds 2 and 4–11) from solid defined medium. The structures of the seven new compounds, eutypelleudesmane A (1), cytosporin Y (2), cytosporin Z (3), cytosporin Y1 (4), cytosporin Y2 (5), cytosporin Y3 (6), and cytosporin E1 (7), were elucidated by analyzing their detailed spectroscopic data. Structurally, cytosporin Y1 (4) may be a key intermediate in the biosynthesis of the isolated cytosporins, rather than an end product. Compound 1 contained a unique skeleton formed by the ester linkage of two moieties, cytosporin F (12) and the eudesmane-type sesquiterpene dihydroalanto glycol. Additionally, the occurrence of cyclic carbonate moieties in compounds 6 and 7 was found to be rare in nature. The antibacterial, immunosuppressive, and cytotoxic activities of all compounds derived from Eutypella sp. D-1 were evaluated. Unfortunately, only compounds 3, 6, 8, and 10–11 displayed immunosuppressive activity, with inhibitory rates of 62.9%, 59.5%, 67.8%, 55.8%, and 68.7%, respectively, at a concentration of 5 μg/mL.